Design Methodologies of InP nanopyramid array based low cost hybrid solar cells. (2022) - Kumar Agnihotri, Suneet; Prashant, D.V.; Samajdar, D.P.
Abstract: In recent years, the use of organic materials have gained the interest for photovoltaic (PV) applications owing to its ability to yield maximum throughput, solution phase processes, thereby resulting in low cost power generation. To obtain the twin benefits of low cost and high efficiency, PV cell researchers are investigating the organic–inorganic (hybrid) based solar cells (SCs). Hybrid Solar cells (HSCs) combine organic and inorganic materials in order to make use of the relatively inexpensive manufacturing of organic photovoltaics (OPV) and gaining multiple benefits from the inorganic component, such as tunable optical properties, superior electronic properties and high power conversion efficiency (PCE). III-V based nanostructures showed exceptional light capturing and charge transport properties, and can be easily combined with organic materials to build HSCs. In this paper, we have investigated the optical and electrical properties of the PTB7:PC71 BM/InP truncated nanopyramid (TNP) array based HSC. The investigated structure shows higher optical absorption and optical current density (Jsc ) of ∼ 25.4 mA/cm 2 when compared to their organic and inorganic counterparts. The photogeneration profile and electric field of the inorganic and HSC are simulated and compared. In addition, the electrical analysis of HSC shows PCE of 18.4% which outperforms their organic and inorganic counterparts.